The Effectiveness of Using the SQ3R Strategy as an Effort to Improve Students’ Reading Literacy - Falisha Adzra; Shananda Salsabila Hantari; Muhammad Risqi Aditya Kurniawan; Fira Hanifah; Nawa Barirotuzzakiyyah; Trinil Dwi Turistiani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Reading literacy is a fundamental competency essential for students to support their success in higher education. However, students' reading literacy skills are currently relatively low and require serious attention. This study aims to describe the effectiveness of using the SQ3R (Survey, Question, Read, Repeat, Review) strategy to improve students' reading literacy skills. This study used a descriptive qualitative approach. Data collection was conducted through a pretest instrument in the form of a questionnaire distributed online via Google Forms to randomly selected students (random sampling) without institutional restrictions. The data obtained were then analyzed descriptively to describe the initial state of students' reading literacy and their perceptions of the implementation of the SQ3R strategy. The results indicate that most students have not yet implemented a systematic reading strategy in their academic activities. The SQ3R strategy is considered relevant and has significant potential to help students understand texts more deeply, improve critical thinking, and develop structured reading habits. This study recommends broader implementation of the SQ3R strategy in higher education as a concrete solution to improve the quality of students' reading literacy.